2018
DOI: 10.3390/medsci6010005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Traumatic Endotheliopathy in Isolated Severe Brain Injury and Its Impact on Clinical Outcome

Abstract: Study design: Prospective observational cohort. Objective: To investigate the difference in plasma levels of syndecan-1 (due to glycocalyx degradation) and soluble thrombomodulin (due to endothelial damage) in isolated severe traumatic brain injury (TBI) patients with/without early coagulopathy. A secondary objective was to compare the effects of the degree of TBI endotheliopathy on hospital mortality among patients with TBI-associated coagulopathy (TBI-AC). Methods: Data was prospectively collected on isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…35 36 In addition, excessive consumption of coagulation factors and platelet dysfunction, 37 hypoperfusion and protein-C pathway activation, hypothermia, metabolic acidosis and haemodilution can also lead to coagulation dysfunction after TBI. 38 In patients with TBI, the blood-brain barrier is destroyed; Fbg and its degradation products enter the brain and activate the inflammatory reaction cascade and the immune response in the brain, leading to lymphocyte infiltration, glial cell activation, cytokine release and reactive oxygen element production in the brain. These lead to axonal demyelination and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…35 36 In addition, excessive consumption of coagulation factors and platelet dysfunction, 37 hypoperfusion and protein-C pathway activation, hypothermia, metabolic acidosis and haemodilution can also lead to coagulation dysfunction after TBI. 38 In patients with TBI, the blood-brain barrier is destroyed; Fbg and its degradation products enter the brain and activate the inflammatory reaction cascade and the immune response in the brain, leading to lymphocyte infiltration, glial cell activation, cytokine release and reactive oxygen element production in the brain. These lead to axonal demyelination and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in mice have shown that the inflammatory response to toxins, chemicals, allergens and pathogens is dysregulated in the absence of Sdc1 or when its shedding is inhibited (Kainulainen et al ., ; Kato et al ., ), suggesting that Sdc1 shedding is activated to ensure adequate tissue response to inflammation. Consequently, Sdc1 has been proposed to be a biomarker for sepsis survival after major abdominal surgery, as well as for acute traumatic endotheliopathy in isolated severe brain injury, and for small bowel mucosal damage in children with celiac disease (Yablecovitch et al ., ; Albert et al ., ; Holzmann et al ., ).…”
Section: Shed Syndecans As Biomarkers For Different Diseasesmentioning
confidence: 99%
“…The shedding of syndecan-1 indicates the depletion of protective glycocalyx, also making the endothelium more procoagulant 26 . A study found that patients with TBI-IC had lower plasma levels of soluble thrombomodulin and higher levels of soluble syndecan-1, as compared with patients without coagulopathy 27 . Extracellular vesicles (EVs) released from injured endothelial cells are also increasingly used as a marker for plasma procoagulant activity because they are associated with endothelial injury and also express procoagulant activity 17,28,29 .…”
Section: Tests For Tbi-icmentioning
confidence: 99%